Constructivist basis of project model in teaching science - Ristanović, Dušan P. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In this paper are explained the theoretical methodological basis of project model in science teaching, in the light of constructivist understanding of learning processed teaching. Author, by using the method of theoretic analysis and modeling, brought up the interpretation of the key characteristics of this model, based on a constructivist approach: active student`s involving – providing surrounding and situations I which students will actively create their knowledge, applying knowledge – complexed process which includes using and developing existing knowledge, using different sources of knowing, projecting and concluding the researches, applying knowledge in new situations, reflection and improving theirs own environment, different forms for presenting the results, learning community – social context of learning as co-construction of knowledge and authentic tasks – problem based questions which are relevant to students and are connected to life outside the school. In this paper is concluded that respecting of constructivist standpoint presents essential condition for adequate implementation of project model in teaching science. Disrespecting of this condition may lead to routine organization and realization, similar to traditional teaching model.